Originally Posted by

**pencil09** find$\displaystyle a(x-h)^2+k$form first....

$\displaystyle ax^2+b x+c=0$ (divided by $\displaystyle a$)

$\displaystyle x^2+\frac{b}{a} x+ \frac {c}{a}=0$(substract by $\displaystyle \frac {c}{a}$)

$\displaystyle x^2+\frac{b}{a} x =-\frac {c}{a}$ (add by $\displaystyle (\frac {b}{2a})^2$)

$\displaystyle (x+\frac{b}{2a})^2=-\frac {c}{a}+(\frac {b}{2a})^2$

$\displaystyle (x+\frac{b}{2a})^2+(\frac {c}{a}-(\frac {b}{2a})^2)=0$

so,

$\displaystyle h=-\frac{b}{2a}$

$\displaystyle k=(\frac {c}{a}-(\frac {b}{2a})^2)$

or $\displaystyle k=-\frac{b^2-4ac}{4a^2}$

-----I hope it'll help U-----